Relationship of Arrhythmogenic Substrate and Frequent Ventricular Extrasystoles in Patients with Nonischemic Cardiomyopathy - Dietrich, Cristiano de Oliveira (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Cardiomyopathies (CMP) are related with scarring tissue due to fibrotic and disarrangement of myocardial fibers that promote an slowed conduction and substrate for sustained reentrant ventricular arrhythmias. Sometimes, CMP can be associated with ventricular extrasystoles but uncommonly originated from scarring tissue. The case report show a patient with nonischemic CMP, frequents premature ventricular contractions and sustained ventricular tachycardia submitted to catheter ablation.